Improvement Mechanism of Work Oriented by Ergonomic Increase Health Quality and Productivity - Arnita, Ni Putu Sri; Adiputra, Nyoman; Purnawati, Susy; Sucipta, I Nyoman; Sutajaya, I Made; Ratna Sundari, Luh Putu (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2020)
The aim of this research is to reduce musculoskeletal disorders, work stress, and increase productivity of workers piranti upakara makers by work mechanism improvement using ergonomic work oriented. Through a quasi-experimental using treatment by subject design and randomized pre and post-test group design assessed: (a) improvement mechanism of work oriented by ergonomic reducing musculoskeletal disorders, was recorded by Nordic Body Map Questionnaire; (b) improvement mechanism of work oriented by ergonomic reducing work stress, was recorded by Work Stress Questionnaire; (c) improvement mechanism of work oriented by ergonomic increase the productivity of workers, assessed by output (product produced) divided by input (pulse) multiplied by time. Data collection was done at 10 (ten) days before and after working, in Period I and Period II on 14 samples. Data obtained were analyzed using paired t-test at a significance level of 5%. The result showed that improvement mechanism of work oriented by ergonomic, reducing musculoskeletal disorders of workers to 44.45%, reducing the work stress of workers to 29.90%, and increasing productivity of workers to 53.93%. It can be concluded that improvement mechanism of work oriented by ergonomic reducing musculoskeletal disorders, work stress, and improving productivity of workers piranti upakara makers.